Sharing democracy - Ferguson, Michaele L., 1973- (New York ; Oxford : Oxford University Press, 2012)
Democratic theorists frequently assume that the 'people' must have something in common, or else democracy will fail. This produces an ironically anti-democratic tendency to emphasize the passive possession of commonality. Sharing Democracy counters this tendency with a radical vision of democracy grounded instead in the active exercise of political freedom.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Democracy -- Philosophy; Group identity -- Political aspects; Identity politics; Identity (Philosophical concept); Agent (Philosophy)